Penerapan Model Pembelajaran Project Based Learning Melalui Media Vlog Untuk Meningkatkan Minat Belajar Dan Prestasi Belajar Siswa - Nining Masrucha; I Gusti Ayu Agung Sinta Diarini; I Wayan Suryanto (Jayapangus Press, 2021)
Purpose of this study is: To find out whether the application of learning model project based learning through vlog media is able to increase student interest in learning, and student achievement and is able to jointly increase the interest in learning and achievement of class XI Catering 5 students in the subject of food and beverage servicee at SMK Negeri 2 Tabanan. This type of research is classroom action research (CAR) with quantitative descriptive data analysis techniques. The object of research is interest in learning and student achievement and the sample in this study was class XI Catering 5 SMK Negeri 2 Tabanan. The results showed that learning achievement has increased supported by an increase in student learning outcomes. This is supported by the successful application of themodel project based learning through vlog media which has an effect on increasing student interest in learning which is shown from feelings of pleasure, student involvement, interest, and attention of students. This also proves that the application of themodel project-based learning through vlog media has succeeded in increasing student interest in learning and learning achievement.